Serology suggests adequate safety measures to protect healthcare workers from COVID-19 in Shiga Prefecture, Japan - Chano, Tokuhiro; Morita, Shin-ya; Suzuki, Tomoyuki; Yamashita, Tomoko; Fujimura, Hirokazu; Yuri, Tatsushi; Menju, Masakazu; Tanaka, Masaaki; Kakuno, Fumihiko (PloS one, 2022)
Healthcare workers (HCWs), especially frontline workers against coronavirus disease 2019 (COVID-19), are considered to be risky because of occupational exposure to infected patients. This study evaluated the correlation between seroprevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies among HCWs and the implementation of personal protective equipment (PPE) & infection prevention and control (IPC). We recruited 1237 HCWs from nine public COVID-19-designated hospitals in Shiga Prefecture, central Japan, between 15–26 February 2021. All participants answered a self-administered questionnaire and provided blood samples to evaluate SARS-CoV-2 antibodies. A total of 22 cases (1·78%) were seropositive among the 1237 study participants. An unavoidable outbreak of SARS-CoV-2 had occurred at the terminal care unit of one hospital, before identifying and securely isolating this cluster of cases. Excluding with this cluster, 0·68% of HCWs were suspected to have had previous SARS-CoV-2 infections. Binomial logistic regression from individual questionnaires and seropositivity predicted a significant correlation with N95 mask implementation under aerosol conditions (p = 8.63e -06 , aOR = 2.47) and work duration in a red zone (p = 2.61e -04 , aOR = 1.99). The institutional questionnaire suggested that IPC education was correlated with reduced seropositivity at hospitals. Seroprevalence and questionnaire analyses among HCWs indicated that secure implementation of PPE and re-education of IPC are essential to prevent SARS-CoV-2 infection within healthcare facilities. Occupational infections from SARS-CoV-2 in healthcare settings could be prevented by adhering to adequate measures and appropriate use of PPE. With these measures securely implemented, HCWs should not be considered against as significantly risky or dirty by local communities.